THE ARCHETYPE OF MOTHERHOOD REFLECTED IN THE CHARACTER OF MOTHER IN NIKI CARO’S THE MOTHER (2023) - Afsa, Nyemas Nabila; Ariyani, Latifah Dwi (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2024)
This study aims to analyze: (1) the archetype of motherhood reflected in the character of mother and (2) the role of mother psychological perspective of the character of mother in Niki Caro's “The Mother” (2023). The study uses descriptive qualitative method. Data collection from this research method includes watching and reading, identifying, classifying, and selecting. Data analysis of this research method by displaying, explaining, and interpreting using the psychoanalysis theory of Carl Gustav Jung and the relevant approaches related to the archetype of motherhood. The result of the study: (1) the archetype of motherhood reflected in the character of mother in Niki Caro’s “The Mother” (2023) is the representation of the archetype of motherhood about tenderness and affection.; (2) the role of mother psychological perspective of the character of mother is found in various archetypal types namely Persona, mothers often cover up reality in order to see the safety of their daughters; Shadow, the mother character is not only a loving woman but also full of ambition; Anima and Animus (syzygy), The mother character has another archetype namely animus, the mother is like a man, she is a strong woman and never fragile; Hero, The mother character also has the ability to be a hero because she always helps her coworkers and children; Self, The mother character also has a desire for herself.